Climatic response of Cedrela fissilis radial growth in the Ombrophilous Mixed Forest, Paraná, Brazil. - MARCON, A. K. (2019)
We examined the climatic response of Cedrela fissilis radial growth based on precipitation, air relative humidity, temperature and monthly thermal amplitude. It was intended to assess how the secondary growth of C. fissilis is influenced by the climatic variables and which one are the best growth predictors in Ombrophilous Mixed Forest, southern Brazil. Wood cores were processed using classical dendrochronology methodology. Principal Components Analysis, Generalized Linear Models and correlation were used to explore the relationship between radial growth and climate. Our results indicated that the best radial growth predictor is the temperature: the seasonal behavior, under well-watered conditions, seems to have a dominant effect on growth responses. Changes in tree growth corresponding to an increase in temperatures suggest a sensitivity of the species to climate changes. These results are important to help understand how the global warming may influence long-lived pioneer tree growth.